ChemInform Abstract: Co‐Catalyzed Cross‐Coupling of Alkyl Halides with Tertiary Alkyl Grignard Reagents Using a 1, 3‐Butadiene Additive. Issue 50 (10th December 2013) - Iwasaki, Takanori; Takagawa, Hiroaki; Singh, Surya P.; Kuniyasu, Hitoshi; Kambe, Nobuaki
Abstract The use of isoprene and LiI is essential for the high yields of the reactions.